The Role of the Regional Office of the Ministry of Law and Human Rights in Notary Supervision at the Regional Level - Panjaitan, Leyla Vani; Simamora, Janpatar (Golden Ratio of Data in Summary, 2025)
This study discusses the role of the Regional Office of the Ministry of Law and Human Rights (Kemkumham) in the supervision of notaries in Indonesia, which is regulated by Law number of notaries reaching 19 109 people, the Ministry of Law and Human Rights is committed to improving the quality of legal services through continuous coaching and supervision. The Notary Supervisory Council is a supervisory institution that ensures notaries carry out their duties through regulations and codes of ethics. This research also highlights the importance of establishing a Notary Legal Problem Investigation Team to handle public complaints efficiently. Through strict supervision, it is hoped that the professionalism of notaries can be maintained to provide optimal legal protection for people who use notary services.